POSTCOLONIAL MELANCHOLY AND FEMINIST AESTHETICS IN SITI RUKIAH’S 1950 NOVEL KEJATUHAN DAN HATI: A SUBVERSIVE TENDERNESS - Dewi Candraningrum; Titis Setyabudi; Kania Bening Rahmayna (Adabiyyāt: Jurnal Bahasa dan Sastra, 2025)
This study reexamines Kejatuhan dan Hati (1950) by Siti Rukiah Kertapati as a foundational yet neglected work in Indonesian literary modernity. Departing from the masculinist and nationalist revolutionary narratives of its time, the novel articulates postcolonial melancholy through emotional interiority, intimate loss, and the crisis of female subjectivity. Using qualitative textual analysis informed by feminist narratology and postcolonial theory, the study investigates how Rukiah’s fragmented, epistolary form constructs a feminine interiority that resists nationalist and patriarchal ideologies. The analysis draws on the critiques of gendered silencing by Chandra Talpade Mohanty and Trinh T. Minh-ha to interpret Susi’s psychological fragmentation as an act of affective and epistemic resistance. The results reveal that Rukiah transforms vulnerability and melancholy into political agency, redefining emotion as a site of historical meaning. Her narrative techniques—fragmentation, introspection, and affective honesty—subvert the masculine heroism of socialist realism, asserting tenderness as a radical feminist aesthetic. The article also traces the novel’s critical reception, from early marginalization to later reevaluation by scholars such as Annabel Teh Gallop and Yerry Wirawan. As an affective archive of postcolonial disillusionment and feminine resistance, Kejatuhan dan Hati emerges as a politically potent reimagining of nationhood through gendered emotion.